HR ANALYTICS: INSIGHTS FROM LITERATURE (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
HR analytics is being adopted by organizations  and its importance has steadily increased to  become more of a necessity. Since it is an  emerging topic, this paper aims to present  an overview of HR analytics’ content, scope,  significance, opportunities and challenges in  its applications. The methodology adopted was  review of literature from 144 articles including  62 peer-reviewed ones selected from online  search of three large databases with the terms  ‘human resource/ workforce/ people/ talent  analytics’, ‘human capital analytics and metrics’  and ‘predictive human resource analytics’. The study finds that HR analytics, as a concept, is  still a developing one with further strengthening  required on its several aspects. Analytics cannot  replace HR but can definitely assist HR  professionals in discharging their roles in an  improved manner. The primary objective of HR  analytics is to increase organizational effectiveness  by way of better data-based managerial decisions.  However, evidence about usage of HR analytics  is limited. A universally acceptable definition  for it is a potential area for research. The factors  responsible for its adoption in general as well as in  different research settings also need to be studied.
Keywords: HR analytics; workforce; human capital trends; evidence based decisions; descriptive; prescriptive; organizational effectiveness